2010
DOI: 10.1089/thy.2009.0213
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Dynamics of 99mTc-Pertechnetate Uptake in the Thyroid and Other Organs Assessed by Single-Photon Emission Computed Tomography in Living Mice

Abstract: AcknowledgementsAsLing wishes to thank and acknowledge the support of the sponsors of TC39: Gold SponsorSilver Sponsor Silver Sponsor Exhibitor Media Sponsoriii Preface For the past 39 years the international conference, Translating and the Computer (TC), has been a unique forum for academics, users, developers and vendors of translation technology tools. It is a distinctive event where translators, interpreters, researchers and business people, from translation companies, international organisations, universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 38 publications
(18 reference statements)
1
29
0
Order By: Relevance
“…Although several different reporter genes are available (6), we chose NIS because its tracers are widely available without specialist radiochemistry facilities and at comparatively low cost, there are tracers for both SPECT and PET (6,(14)(15)(16), and tracer metabolism and clearance are well understood. In our case, the sensitivity depends on NIS expression levels and function and percentage of NIS-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although several different reporter genes are available (6), we chose NIS because its tracers are widely available without specialist radiochemistry facilities and at comparatively low cost, there are tracers for both SPECT and PET (6,(14)(15)(16), and tracer metabolism and clearance are well understood. In our case, the sensitivity depends on NIS expression levels and function and percentage of NIS-positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a tomographic technique, such as SPECT, is needed to achieve the level of spatial resolution required (23).…”
Section: Discussionmentioning
confidence: 99%
“…This enhances the 4 hour thyroid RAIU from about 3.5% to 27% and makes thyroid scintigraphy, at all acquisition times, brighter and more detailed (46). SPECT studies in mice using 99m Tc or 123 I have also been reported (55,56).…”
Section: Commentarymentioning
confidence: 96%